National cardiac registries: a systematic review. (25th November 2020) - Dawson, L; Biswas, S; Stub, D; Lefkovits, J; Burchill, L; Reid, C; Eccleston, D
Abstract: Background: Over the last thirty years, there has been exponential growth in the number and scale of national cardiovascular disease registries. We aimed to provide a comprehensive outline of contemporary national cardiac registries across all subspecialties. Methods: We performed a systematic literature review by searching OvidMedline in August 2019 to identify registries relating to six pre-specified domains (Table). For inclusion, registries had to be national in nature, actively collecting data, and publishing either peer-reviewed publications or online reports. Results: A total of 24, 076 records were identified from six domain-specific Medline searches; 24, 057 abstracts were screened with 19, 435 non-relevant records excluded; 4, 624 full texts were screened with 4, 473 non-relevant texts excluded; and 151 registries met inclusion criteria representing 51 countries. Of these, 15 related to cardiac surgery, 27 to arrhythmia (17 device, 5 ablation, 7 atrial fibrillation), 21 to congenital heart disease (14 general, 2 interventional, 4 surgical, and 1 disease specific), 43 to coronary disease or percutaneous coronary intervention (22 PCI, 21 CAD), 27 to heart failure (13 heart failure, 5 transplant, 2 mechanical support, 7 disease specific), and 18 related to structural intervention (3 any, 13 transcatheter aortic valve replacement, 2 mitral intervention). Nine national registries (USA, Sweden, Finland, Denmark, UK, Portugal, Norway, Taiwan, and Singapore) covered multiple domains. Quality scoring using the Monash University Clinical Quality Registry Grading System (a composite score of recruitment, and data completeness, definitions, reliability and validation), demonstrated marked heterogeneity in quality between registries. Conclusions: Cardiac registries have seen rapid growth, however the use and quality among various subspecialties differs markedly across world regions. Given the multiple benefits, clinicians, funders and health bureaucrats should be encouraged to focus on the range, quality and uptake of national registries. Funding Acknowledgement: Type of funding source: None